Aspects of Ortega y Gasset in the formation of citizens - Rumayor, Miguel (Revista Complutense de Educación, 2016)
José Ortega y Gasset cannot be classified as theorist or philosopher of education, although his works possess important reflections in this field of knowledge. Specifically, this article highlights the value of the raciovitalist philosophy and the formation of citizens in the personal perspective, which will contribute to the construction of society and democratic life. In addition to this, in light of the political liberalism of this author, this article analyzes, among others, his important ideas about freedom, patriotism, citizenship, elegance and tolerance, as great conceptual contributions to the educational task. Basically all thought of Ortega will be focused on deeply shaping the personal intimacy of citizens. This element is displayed as the center and the goal of education, and all social and personal aspects of the formation of citizens spinning exposed in the writing spinning around this idea, are analyzed in this paper.
Keywords: education of citizens; Ortega y Gasset; moral education; education of intimacy; education for democracy